PENGARUH PEMBELAJARAN PENDIDIKAN PANCASILA DAN KEWARGANEGARAAN TERHADAP PEMBENTUKAN CIVIC DISPOSITION (WATAK KEWARGANEGARAAN) SISWA DI SMA NEGERI 1 DAYUN KECAMATAN DAYUN KABUPATEN SIAK - Edi Prasetyo; Hambali '; Gimin ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: the background of this research is the weakness of Nation character. The Nation character is becoming very important and to be the basis for the existance of the Nation of Indonesia. Especially when facing the reality, that Indonesia is going to the Global era. For Indonesian as a society of the developing countries, the variety of culture social problem are rising up, either anomie (social sickness) as identity lost, or cultural shock (the future shock). These are happened as an effect of the friction of the old relationship pattern that limited by geography, culture, and the country is becoming a new system that has transnational, transcultural, and multicultural character. This is should be the rising of PKn to locate itself as a factor of the puller of the nation character building to be able in preparing young citizens those have character of Indonesia and to be united to develop Indonesia. Therefor, the formulation of the problem of this research is how the effect Civic Education towards the civic disposition building of the students of SMA N 1 Dayun of Dayun Subdistrict of Siak Regency. The research method used a quantitaive descriptive research. The data collecting Instrument used questionaire that consisted of 35 questions about civic education (X variable) and 37 questions about civic disposition (variable Y) to 25 respondents . data analize used a simple linear regression. Thus, hyphothesis “ there is an effect of civic education towards civic disposition building of the students of Sma N 1 Dayun Of Dayun Subdistrict Of Siak Regency is accepted. This is proved by the numbers of simpe linear regression tests between X variable and Y variable, obtained Fcount 8,513 and F table 4,28 from Ftable distribution with N: 25, at significant level 5 %, therefor, Fcount ≥ Ftable, or 8,513 ≥ 4,28.Keywords: Civic Education towards, Civic Disposition building